Unprovoked Venous Thrombosis Following COVID-19 Vaccination: A Retrospective Analysis of the Role of mRNA Vaccines - Mohammed, Abdul Moqeeth; Fatima, Ayesha; Alamin, Mohammed A.; Haider, Vajeeha; Bakhsh, Nadia Karim; Abdelgelil, Mohamed Salem; Al-Khal, Abdullatif; Elzouki, Abdel-Naser (Ibnosina Journal of Medicine and Biomedical Sciences, 2025)
Despite the effectiveness of COVID-19 vaccines in combating the infection through neutralizing antibodies, several side effects have been documented. Vigilant drug safety surveillance has gathered reports on vaccine-induced adverse effects, mainly mild to moderate in severity. Rarely, severe adverse effects such as anaphylaxis, thrombosis, and thrombocytopenia have been observed. Among these, thrombosis emerged as a particularly concerning issue.This has prompted an investigation into the potential existence of a valid link between the vaccine and the occurrence of thrombosis.This case series is aimed to assess clinical features of venous thrombosis after injection of two anti-COVID-19 vaccines: the Pfizer-bioNTech vaccine (BNT162b2) and the Moderna (mRNA-1273) vaccine.We summarized all the salient demographic and clinical features, vaccination details, laboratory investigations, and outcomes. The individual cases are highlighted in more detail. In this case series involving seven patients, we observed rare adverse effects of venous thromboembolism (VTE) following COVID-19 vaccinations of mRNA vaccines, including Pfizer-bioNTech and Moderna.While our findings addressed the rare adverse effect of VTE postvaccination, it is crucial to recognize the overall benefits of these vaccines in combating the COVID-19 pandemic. The underlying mechanism behind thromboembolism due to mRNA vaccines remains uncertain, distinguishing these cases from those related to adenovirus-based vaccines. More studies will be needed to establish if any relation exists.
Keywords: COVID-19; management; prognosis; thrombosis; unprovoked thrombosis